Study of lncRNA TPA in Promoting Invasion and Metastasis of Breast Cancer Mediated by TGF-β Signaling Pathway - Li, Qinglin; Mo, Wenju; Ding, Yuqin; Ding, Xiaowen (Frontiers in Cell and Developmental Biology, 2021)
Purpose: This study was to investigate the effects of lncRNA TPA overexpression and knockdown stable cell lines on the EMT, migration and invasion capabilities of breast cancer cells. Methods: WB and qRT-PCR were used to detect the expression of E-cadherin, Vimentin, fibronectin and N-cadherin, the key molecules of EMT, to determine whether lncRNA regulates EMT; The effect of lncRNA TPA on the migration and invasion of breast cancer cells was detected by scratch, migration and invasion assay. The effect of lncRNA TPA on breast cancer metastasis was studied in nude mice model to observe whether lncRNA TPA affected breast cancer metastasis. Pierce Magnetic RNA-Protein Pull-Down Kit was used to bind the 3 '-terminal desulfurized biotin-labeled lncRNA TPA with Magnetic beads, and then incubated with the proteins extracted from cell line C and D respectively. After elution of the binding proteins, the interacting proteins were further identified by mass spectrometry to screen out the interacting proteins. The candidate proteins were expressed and purified in vitro, and the interaction between lncRNA-candidate proteins was verified by RNA-EMSA. Results: Overexpression of lncRNA TPA decreased the expression of E-cadherin, and significantly increased the expression of Vimentin, fibronectin and TGF-β1 (p<0.01), and increased the migration rate, migration ability and invasion ability of cell group (P<0.01). Multiple lung metastases were observed in the lung tissue of nude mice with overexpression of lncRNA TPA. Conclusions: LncRNA TPA affects the occurrence of breast cancer EMT through TGF-β signaling pathway, and then promotes the invasion and metastasis of breast cancer. LncRNA TPA may affect the corresponding signaling pathways through one or more interacting proteins, and ultimately promote the invasion and metastasis of breast cancer.